1939
DOI: 10.1029/tr020i004p00637
|View full text |Cite
|
Sign up to set email alerts
|

The relation of suspended to bed material in rivers

Abstract: It has been known for some time that if the average concentration of suspended sediment at any point in a wide straight stream was known, the average concentration at any other point could be determined. This was first demonstrated by O'Brien ]see 1 of ”Bibliography“ at end of paper] using the methods developed by Schmidt in a study of turbulence in the atmosphere. That the results obtained with this method agree with actual observations in streams and channels was demonstrated by Christiansen ]2[ and Richards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Circulation and viscosity are imperative parameters of the analysis. Lane and Kalinske (1939) stressed on turbulence for the determination of lift and assumed that: (a) particles that have a settling velocity smaller than the instantaneous vertical velocity fluctuations in the vicinity of the bed experience lift; (b) the velocity fluctuations vary following the normal-error law; and (c) the velocity fluctuations and shear velocities are correlated. White (1940) carried out a single experiment and found that the lift on an individual particle is very small compared to its weight.…”
Section: Lift Force Conceptmentioning
confidence: 99%
“…Circulation and viscosity are imperative parameters of the analysis. Lane and Kalinske (1939) stressed on turbulence for the determination of lift and assumed that: (a) particles that have a settling velocity smaller than the instantaneous vertical velocity fluctuations in the vicinity of the bed experience lift; (b) the velocity fluctuations vary following the normal-error law; and (c) the velocity fluctuations and shear velocities are correlated. White (1940) carried out a single experiment and found that the lift on an individual particle is very small compared to its weight.…”
Section: Lift Force Conceptmentioning
confidence: 99%
“…(I) are transported as bed load, those with smaller w~ values move in suspension. Various values of the critical k have been used: k = 1.00 (Lane and Kalinske, 1939;Inman, 1949;Francis, 1973: Middleton, 1976, k = 1.20 (Einstein, 1950), k = 1.25 (Bagnold, 1966) and k = 1.79 (McCave, 1971). This range of k values is in part due to the rather arbitrary nature of the distinction between bed load and suspension transport.…”
Section: Bed-load Versus Suspension Transportmentioning
confidence: 99%
“…The deficiency concerns the relationship of y to characteristics of the sediment, the flow and the bed. There are semiempirical relationships, such as that of Lane and Kalinske (1939), for predicting the conditions necessary for entrainment. However, none of them are capable of predicting in a probabilistic sense how long a particle will remain on the bed before it is entrained.…”
Section: -E -Ytmentioning
confidence: 99%